(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the psychological and pedagogical factors of the formation of learning motivation in primary school students. The essence of learning motivation, its role in the development of children of primary school age and its importance in the educational process are highlighted. The role of the teacher’s pedagogical skills, teaching methods, positive psychological environment and encouragement in increasing students’ interest in learning is also considered. The article substantiates effective pedagogical approaches that serve to form stable learning motivation in primary school students, as well as psychological conditions.